Allium Sativum (Garlic) Extract as Nontoxic Corrosion Inhibitor - K. Rajam; S. Rajendran; R. Saranya (Journal of Chemistry)
The inhibition efficiency (IE) of an aqueous extract of garlic in controlling corrosion of carbon steel in well water in the absence and presence of Zn2+ has been evaluated by mass-loss method. The formulation consisting of 2 mL of garlic extract and 25 ppm Zn2+ offers 70% inhibition efficiency to carbon steel immersed in well water. Polarization study reveals that this formulation controls the anodic reaction predominantly. FTIR spectra reveal that the protective film consists of Fe2+-allicin complex and Zn(OH)2.